Elia Wilkinson Peattie papers - Peattie, Elia Wilkinson, 1862-1935.; Peattie, Donald Culross, 1898-1964.; Peattie, Robert Burns, 1857-1930.
Chiefly autobiographical and biographical writings by Peattie, her husband Robert Burns Peattie, and their son Donald Culross Peattie. Elia Peattie's autobiography concerns her childhood on a farm in southwestern Michigan, journalism career, involvement in the women's club movement, and family. Robert Peattie's autobiography describes his childhood in Chicago, the Chicago fire, his journalism career, and Abraham Lincoln's assassination. Includes biographical material on Donald Culross Peattie; Olive Child pertaining chiefly to her childhood in Saratoga, N.Y., during the early 19th century; and Alfred Payne concerning his career as a portrait painter.
Journalist, writer, and women's club activist. Died 1935.
Collection material in English.
Keywords: Child, Olive; Lincoln, Abraham, -- 1809-1865 -- Assassination; Payne, Alfred, -- -1893.; Farm life -- Michigan; Great Fire, Chicago, Ill., 1871.; Journalism -- United States; Portrait painting, American -- 19th century; Women -- Societies and clubs; Chicago (Ill.) -- History -- To 1875.; Chicago (Ill.) -- Social life and customs; Michigan -- Social life and customs; New York (State) -- Social life and customs; Saratoga (N.Y.) -- Social life and customs; Peattie family; Authors; Journalists; Social activists